Dampak Suasana Sekolah dalam Meningkatkan Motivasi Belajar Pendidikan Agama Islam di Era Digital Siswa Kelas XI SMK Cendikia Bontang Tahun Pelajaran 2023/2024 - Satriani, Satriani; Aslam, Muhammad (NABAWI: Jurnal Penelitian Pendidikan Islam, 2024)
The school environment refers to the control of social dynamics or educational arrangements; a positive school environment is essential for motivating students to learn. With this in mind, a study was conducted to analyze the impact of the school environment on students' learning motivation. The research was carried out at SMK Cendikia Bontang, with the subjects being 11th-grade students. Using a qualitative research method, data were collected through observation, interviews, and documentation. The findings indicate that the school environment significantly influences the improvement of learning motivation, particularly in the current digital era. The results show a significant positive change in the learning motivation of 11th-grade students at SMK Cendikia Bontang due to the positive changes in the school environment. The increase in students' motivation to learn Islamic Religious Education (PAI) in the digital era can be seen through the comparison of learning outcomes before and after the study was conducted. Based on these findings, the school environment greatly impacts the learning motivation of 11th-grade students at SMK Cendikia Bontang. The better the school environment, the higher the students' learning motivation, and vice versa.